How to Measure the Customer Purchase Decision in Shopee E -Commerce Platform? - Ikramina Larasati Hazrati Havidz; Hilda Bernika Ningrum; Hazimi Bimaruci Hazrati Havidz; Riza Rizqiyah (Majalah Ilmiah Bijak, 2023)
The study aims to pictured out the mediating roles Â of purchase intention on service quality and application quality to purchase decision. The study objective is the shopee application users with at least 1 year of experience using the application. The study collected 140 respondents. Smart-PLS will be used to run the data. The study signified service quality and application quality have a positive and significant influence on purchase intention. Service quality and application quality have a positive and significant influence directly and indirectly on purchase decision. Lastly, Purchase Intention play a mediating role from service quality and application quality on purchase decision.